2019
DOI: 10.1111/hel.12581
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori resistance to clarithromycin and fluoroquinolones in a pediatric population in Turkey: A cross‐sectional study

Abstract: Background Helicobacter pylori antimicrobial resistance is gradually increasing around the world. However, there are a limited number of studies reporting on this issue in the pediatric population. In this study, we aimed to determine H pylori resistance to clarithromycin and fluoroquinolones in the pediatric patients living in Kırıkkale province that were detected with H pylori in gastric biopsies. Moreover, we also aimed to investigate the concordance between the histopathologic and molecular methods used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
1
14
0
3
Order By: Relevance
“…Shu et al recently showed a significant increase in resistance rates for CH, MET and double-resistance to CH and MET in children in China [ 21 ]. Similar observations were made by researchers from Turkey [ 29 ]. In Poland, due to high resistance to CH (>15%), the empirical use of PPIs, MET and AMO in first-line therapy is a standard treatment, although at our center, attempts at targeted treatment based on results of susceptibility testing have been undertaken for several years [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…Shu et al recently showed a significant increase in resistance rates for CH, MET and double-resistance to CH and MET in children in China [ 21 ]. Similar observations were made by researchers from Turkey [ 29 ]. In Poland, due to high resistance to CH (>15%), the empirical use of PPIs, MET and AMO in first-line therapy is a standard treatment, although at our center, attempts at targeted treatment based on results of susceptibility testing have been undertaken for several years [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…Finally, 22 studies were included in this systematic review and meta-analysis (Fig. 1 , Additional file 1 ) [ 12 17 , 19 34 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Three studies used the same commercial molecular assay HelicoDR test (Hain Lifescience, Germany). In the study of Navarro-Jarabo et al, this assay was applied to H. pylori isolates and in the studies of Aguillera-Correa et al and Güven et al, DNA extracted from biopsy samples was tested [ 19 , 22 , 24 ]. Another commercial assay, BACTfish H. pylori Combi kit (Izinta Kft., Hungary) was used to analyse the biopsy specimens [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Keywords: chronic pancreatitis, Helicobacter pylori, eradication therapy В настоящее время основными компонентами схем эрадикационной терапии (ЭТ) инфекции Helicobacter pylori (H. pylori) являются антибактериальные препараты. Исследователи отмечают рост антибиотикорезистентности H. pylori во всем мире [1,2]. Показатель успешности элиминации H. pylori при классической тройной терапии постепенно снижается [3].…”
Section: Discussionunclassified